Fibrinolytic and haemostatic activities of caffeic acid phenethyl ester and propolis from Malaysian stingless bee and romanian poplar in vitro - Abdelrahman Elnager, Abuzar Mahmoud (2015)
Caffeic acid phenethyl ester (CAPE) is a phenolic derivative from propolis and plants. The aims of this study include: (1) Development and validation of an in vitro whole blood (WB) clot lysis procedure for fibrinolytic activity study, (2) Investigation of fibrinolytic, antiplatelet and anticoagulant properties of CAPE, Malaysian Tetratrigona itama (T.itama) and poplar propolis and (3) Determination and quantification of CAPE compound in Malaysian T.itama propolis. The WB clot lysis procedure was developed using a standardized unresected retracted WB clot incubated in pooled platelet poor plasma (PPP) for varying incubation times and successfully validated using streptokinase (SK). The fibrinolyic activity was assessed by D-Dimer (DD), fibrin morphology by confocal microscopy and WB clot weight. DD was measured photometrically by immuno-turbidometric method. Fibrinolytic activity of CAPE, Malaysian T.itama and poplar propolis was assessed by the new WB clot lysis procedure at different concentrations and different times. Platelet activity study of CAPE was performed using different in vitro assays including: 1) Platelet aggregation measurement by platelet aggregometry with different types of agonists, adenosine diphosphate (ADP), arachidonic acid (AA) and ristocetin. 2) Platelet activation markers (PAC-1 and P-selectin) expression by flow cytometry. 3) P2Y12 receptor determination by Western blot (W.blot) technique. The platelet study of Malaysian T.itama and poplar propolis was done by platelet aggregometry. Thromboelastgraphy (TEG) parameters were recorded following WB incubation with CAPE, Malaysian T.itama and poplar propolis. Quantitation of CAPE in propolis was performed by Gas Chromatograph-Mass Spectrometer (GCMS) analysis using constructed calibration curves on peak area versus various concentrations of CAPE. The mean differences of DD (μg/ml) levels were significantly different (p<0.05) across samples incubated with different CAPE concentrations and both types of propolis compared with normal control (PPP). The median pre and post-incubation WB clot weights (gm) were significantly decreased for CAPE, Malaysian T.itama and poplar propolis. Fibrin removal was observed microscopically and indicated dose-dependent effects of CAPE compared with that of normal control at different time. The 50% effective dose (ED50) of CAPE (based on DD) was 1.99 mg/ml. The anti-platelet effect was observed by the techniques used in this study for CAPE and both propolis. The ED50 of CAPE, Malaysian T.itama and poplar propolis (based on platelet aggregation) was 7.31 μg/ml, 0.79 mg/ml and 0.86 mg/ml respectively. TEG results showed fibrinolytic parameter (LY30), was significantly different (p<0.17) from normal control samples incubated in different concentrations of CAPE, Malaysian T.itama and poplar propolis. The antiplatelet effect of CAPE may have contributed to the reduced maximum amplitude (MA) value of TEG assay. The quantity of CAPE measured in Malaysian T.itama and poplar propolis were: 0.6 (0.1) and 29.7 (1.2) mg/g respectively.